Comparison of the Effectiveness of Psychodrama Training and Psychological Empowerment on Anger Control and Distress Tolerance in Incarcerated Women - Esmaeili Dehaghi, Ghazaleh; Ghasemi Pirbalouti, Mohammad; Ahmadi, Reza; kiani, Fariba (Psychology of Woman Journal, 2025)
Objective: The present study aimed to compare the effectiveness of psychodrama training and psychological empowerment on anger control and distress tolerance in incarcerated women. Methods and Materials: The research method was semi-experimental with a pretest-posttest-follow-up design and a control group. The statistical population consisted of women imprisoned in the Nesvan Prison of Isfahan City in 2024. A total of 54 participants were selected through convenience sampling and randomly assigned to three groups of 18 individuals each. The measurement tools included the Spielberger Anger Questionnaire and the Distress Tolerance Scale by Simons and Gaher (2005). The collected data were analyzed at two levels: descriptive statistics (mean and standard deviation) and inferential statistics (repeated measures analysis of variance and Bonferroni post hoc test) using SPSS version 24. Findings: The results indicated that both psychodrama training and psychological empowerment led to an increase in anger control and distress tolerance among the incarcerated women, and this effect persisted during the follow-up stage (p ≤ .05). Furthermore, no significant difference was found between the effectiveness of the two experimental groups (p ≤ .05). Conclusion: Consequently, both interventions can significantly contribute to improving the psychological issues of incarcerated women and preventing recidivism.